Découper la France en régions - Arnaud Brennetot; Sophie de Ruffray (Cybergeo, 2014)
This article offers a comparative analysis of political divisions of French territory proposed between the mid-nineteenth century and the 2010s. The analysis of these regional maps allows us to identify some spatial structures specific to the French regionalist imaginary. Some geographical areas appear repeatedly and seem to be obvious while other areas look more uncertain. Mapping these regional divisions offers a general prism proper to question the new regional units proposed by the president of the French Republic in a bill submitted to Parliament in June 2014.